2020
DOI: 10.1111/1365-2656.13177
|View full text |Cite
|
Sign up to set email alerts
|

Exploring movement decisions: Can Bayesian movement‐state models explain crop consumption behaviour in elephants (Loxodonta africana)?

Abstract: Animal movements towards goals or targets are based upon either maximization of resource acquisition or risk avoidance, and the way animals move can reveal information about their motivation. We use hidden Markov models (HMMs) fitted in a Bayesian framework and hourly Global Positioning System fixes to distinguish animal movements into distinct states and analyse the influence of environmental variables on being in, and switching to, a particular state. Specifically, we apply our models to understand elephant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…1 ). They have recently been used to elucidate spatial memory 44 , detect musth-related movement behavior 45 and explore crop raiding decisions in savannah elephants 30 . We used a gamma distribution to describe the step lengths, a von Mises distribution to describe turning angles, and the Viterbi algorithm to estimate the most likely sequence of movement states to have generated the observations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). They have recently been used to elucidate spatial memory 44 , detect musth-related movement behavior 45 and explore crop raiding decisions in savannah elephants 30 . We used a gamma distribution to describe the step lengths, a von Mises distribution to describe turning angles, and the Viterbi algorithm to estimate the most likely sequence of movement states to have generated the observations.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, ‘exploratory movements’ are long, directionally persistent movements to new locations. The relative amount of time individuals spend in exploratory movements versus resting/foraging (shorter movements with low directional persistence) is important for understanding individual foraging decisions, social interactions and responses to anthropogenic disturbances 29 , 30 . Characterizing these movement behaviors and the factors that influence them is important for effective conservation; for example, to ensure that reserves or corridors are large enough, properly configured, and allow for seasonal and/or anthropogenically-induced behavioral changes.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, fields are more likely to be visited at the end of the growing season when the quality of crops supersedes natural vegetation (Osborn, 2004). Elephant bulls have a greater tendency to raid crops than females (Branco et al, 2019;Vogel et al, 2020;Von Gerhardt et al, 2014) as shown by M1's clear preference for recently deforested patches (Figure 3). There is a notable individual variability related to crop-raiding, whereas M1 and F2 selection patterns are compatible with crop-raiding, F1 and F3 patterns are less clear as they do appear to select these patches but no clear seasonal pattern can be discerned (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Parameter estimations can be performed by the (restricted) maximum likelihood method (Dedieu et al, 2014). However, Bayesian approaches are often preferred for complex models (Vogel et al, 2020). Outputs of the model that would be of interest in genetic studies could include the subject-specific probabilities of hidden states at each time point (these could be replaced by the most likely state for simplicity; Leos-Barajas and Michelot, 2018) and/or the subject-specific initial state and transition probabilities that depict the dynamic change of the animal's behaviour over time.…”
Section: Capture-recapture Analysis To Impute Missing Biter and Victimentioning
confidence: 99%
“…Capture-recapture analysis (CRA) was originally developed to study survival dynamics in wild animal populations (Pradel et al, 1997(Pradel et al, , 2005. Nowadays CRA has applications in many fields of research, including animal activity patterns (Langrock et al, 2012) and movements (Vogel et al, 2020). The principle of this method of survival analysis in wild species is to use data from several independent but overlapping samples to estimate a probability of survival despite the fact that there is missing information.…”
Section: Introduction To the Modelsmentioning
confidence: 99%